The importance of [not] being Miley: Girls making sense of Miley Cyrus. (December 2016) - Jackson, Sue; Goddard, Sarah; Cossens, Sophie
Celebrity as a text of cultural meanings has been widely studied, yet relatively little empirical work has explored celebrity from an audience perspective. This is more emphatically the case for the young teen and pre-teen audience for whom celebrity occupies a central place in their lives. This article investigates the meanings pre-teen girls in three independent studies make of Miley Cyrus who has been a prominent celebrity figure in girls' lives for over a decade. Located at the intersection of girlhood and celebrity studies and using a poststructuralist discursive approach, our examination shows how Cyrus functioned in girls' talk to mark out the boundaries of 'proper' femininity and how these boundaries were informed through both a punitive 'trainwreck' celebrity discourse and an age appropriateness discourse. We argue that the regulatory discourses of girlhood sexuality and femininity that operate in pre-teen girls' lives are crucially important to their negotiation of Cyrus who represents an 'impossible' be-coming for them through her norm-violating hypersexualisation and drug use. The article contributes knowledge about the centrality of gender norms to ways celebrity may be understood and negotiated by girls and disturbs understandings of girl audiences as wholly influenced by, and aspirational towards, the celebrities they engage with.